Tuesday, November 22, 2005

George's 3 question

Substitution
simplify each expression y = 10 z = -4
1) -10(5y+6z-5)+7(8y-4z+3) = ??
2) -3y+2z-6+8y+-6z+19 = ??
3) 2(3y-4z)-5(6y+7z) = ??
Answers:

1) -10(5y+6z-5)+7(8y-4z+3)
simplify
-50y-60z+50+56y-28z+21 =
add the like terms
6y-78z+71 =
change the variable to the given numbers
6(10)-78(-4)+71
60+312+71 =
323
2) -3y+2z-6+8y+-6z+19
add the like terms
5y-4z+13
change the variable to the given numbers
5(10)-4(-4)+13
50+12+13
62+13 =
75
3)2(3y-4z)-5(6y+7z)
simplify
6y-8z-30y-35z
add the like terms
-24y-43z
change the variable to the given number
-24(10)-43(-4)
-240+172 =
68

0 Comments:

Post a Comment

<< Home